Nutrition in Neurologic Disorders : A Practical Guide - Arsava, Ethem Murat (Springer International Publishing : Imprint: Springer, 2017)
This book offers focused and concise coverage of all issues relating to malnutrition in the field of neurology, and in particular addresses practical aspects of nutritional support from a neurology perspective. In addition to providing basic knowledge on important nutritional concepts (body metabolism, assessment and diagnosis of malnutrition, epidemiology, enteral/parenteral nutrition), detailed information is presented on nutritional support for various neurologic disorders handled in a variety of settings, including the neurointensive care unit. Much consideration is also given to the diagnosis and management of dysphagia, which is a common and highly critical cause of malnutrition in these patients. Finally, the newly developing concept of neuronutrition (or brain foods) - the use of certain nutrients for treatment of neurologic disorders - is discussed. By providing practical solutions to commonly encountered challenges in the nutritional management of neurologic patients, this book will prove a valuable resource for practicing neurologists in a wide variety of fields. It will also be very useful for medical personnel from other specialties such as clinical nutrition, critical care, and geriatric medicine.
Keywords: Medicine.; Neurosciences.; Critical care medicine.; Clinical nutrition.; Geriatrics.; Neurology.; Neurosurgery.; elektronické knihy; electronic books